Peran Literasi dalam Mendukung Keterampilan Berpikir Tingkat Tinggi bagi Peserta Didik di Sekolah Dasar Negeri 164/I Sridadi - muhammad toto nugroho; Destrinelli Destrinelli; Agung Rimba Kurniawan; Anggi Pratama; Eka Yuliana; Mia Arfiana; Nurlaili Mulyani (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
The aim of this research is t to understand the role of activities literasi in support of skill reflect critical students grade 5 in state elementary school 164 / I sridadi. The research is the kind of research qualitative ethnography .Resources in this research was , teachers and students with using a technique collection data through interviews, observation. The validity of lab data it uses triangulation method. Existing data analyzed interactive consisting of data collection, reduction data, presentation of data, withdrawal conclusions and verification. Writer can draw conclusions that the literasi having the role that is very effective in improve the ability reflect the high of the aspect of analyze , evaluate and create